PELAKSANAAN PEMBANGUNAN BERTERASKAN ISLAM: KAJIAN KES KOMUNITI ISLAM BAN NUA, HATYAI, THAILAND - Dr. Mohd Shukri Hanapi (Journal of Techno-Social, 2015)
The Ban Nua Muslim community is a Muslim community that is smack in the middle of the non-Muslim community (Buddhist) in Hatyai, Thailand. Although they are a small community and are is such a predicament, they are still able to implement Islamic-based development (IbD). In other words, they are able to develop an Islamic community complete with numerous infrastructures such as a mosque, not only as a place for prayer but it has a clinic, a library, a conference hall, a cooperative and a Zakat Centre (Baitul Zakat). Besides that, this Islamic community has a school that adheres to the Islamic education system. They not only have worked hard to develop the physical aspects but also the spiritual aspects. The physical aspects were developed through general religious servitude such as employment, seeking knowledge, stimulating the community’s economy, business and homestay services, while the spiritual aspects were developed through specific religious servitudes such as prayers, fasting, running the Zakat Centre, reciting the al-Qur’an, devotional recitations (zikr) and giving alms (sadaqah). The question is what tasawwur (worldview) was used to design their development? and how was the tasawwur formed? To answer both these questions, this article has two objectives. First, to identify the tasawwur that has designed the development of the Ban Nua Islamic community; and second, to analyse the developmental worldview of the Ban Nua Islamic community. The findings from the qualitative research had found that the development of the Ban Nua Islamic community in Hatyai, Thailand was designed according to altasawwur al-Islamiy (Islamic worldview). It has three main elements such as ibadah (religious servitude), imarah (general or social leadership) and khalifah (religious leadership). Based on this tasawwur the development of the Ban Nua Islamic community in Hatyai, Thailand was implemented.